Structural prediction and cloning of small, haloacid dehalogenase-like protein of glaciozyma antarctica PI12 in pichia pastoris GS115 - Pauzi, Syaidatul Syazana (2015)
Glaciozyma antarctica PI12 is a psychrophilic yeast isolated from Antarctic sea ice with temperature ranged between -20°C – 15°C near Casey Research Station and its full genome were sequenced. Previously, a scan on its genome for putative phosphatases has led to the discovery of a hypothetical protein termed, LAN_14_281, which contained haloacid dehalogenase-like hydrolase domain. BLAST analysis on this protein showed that it share 58% similarity to haloacid dehalogenase-like protein. Analysis of the protein using SignalP indicates that there is no signal peptide available in LAN_14_281. The constructed phylogenetic tree of LAN_14_281 showed that the protein shares the common ancestors with haloacid dehalogenase-like superfamily. The ProtParam analysis revealed that the theoretical pI for LAN_14_281 are 4.99 with 34 negatively charge residues and 20 positively charged residues. As the role of haloacid dehalogenase can vary and their mechanisms are not fully established, this present study aimed at predicting the structure computationally and cloning of LAN_14_281 for expression and characterization. The 3D structure of LAN_14_281 was built via homology modelling by using the SWISS-MODEL software. The alignment of the protein with 50 templates revealed that the structure has the highest similarity with human haloacid dehalogenase-like hydrolase domain containing protein 1a (Hdhd1a) with 46% sequence identity. Comparison of these two protein structure revealed that the RMSD are 0.421 Å. The 675bp gene sequence encoding LAN_14_281 was synthesized with the incorporation of EcoRl restriction enzymes sites at the 5’ and Xbal restriction enzymes at the 3’ ends. The recombinant plasmid with the genes that codes for LAN_14_281 are cloned into E.coli TOP10 Dh5α for propagation purposes.